FINANCIAL LIABILITIES AND ZAKAT ASSESSMENT - Wan Anisah, Endut; Ahmad, Othman; Suraya, Ismail; Ahmad Azrin, Adnan (2020)
The main purpose of this paper is to examine the financial liabilities treatment in zakat assessment. The existence of the new forms of wealth has now become a challenge for zakat practitioners in dealing with zakat assessments. Therefore, this study seeks to examine financial liability treatment as recommended by JAWHAR and practices at Zakat Institutions in Malaysia for zakat on business and shares. Based on the content analysis, this study found that some zakat institutions in Malaysia allow for the deduction of financial liabilities in the zakat assessment.